Caracterização sensorial e microscópica de queijo tipo camembert elaborado sem mexedura e com adição de concentrados lácteos proteicos - Campos, Sérgio Augusto de Sousa (2016)
Given the complexity and interdependence of the various factors that compose the cheese, its classification is based on the origin of milk, the nature of raw materials, physical and chemical composition and manufacturing technology. However, only those parameters do not fully define the variety of this product. There are special cheeses matured with fungi, wherein the Camembert, white mold cheese, is one of the main representatives of this group. With a progressive commercialization, Camembert cheese favors the competitiveness of the market, propelling changes and technological advances in national production in order to improve sensory and increase the yield. One of the ways used in this production increase is the employment of extenders, including the milk based protein extenders to assign expected sensory attributes and, especially, to improve the final yield. The unique ability of human beings to naturally perceive, compare, describe and classify the sensory properties of a certain product provides to the sensory analysis essential tools to ponder food and drink. Together with the knowledge attributed to sensory analysis, the advanced technique of scanning electron microscopy, a science field that uses the microscope as the main tool, similarly contributes to the characterization of cheeses. The objective of this study was to evaluate the effect of milk protein extenders in the Camembert cheese in sensory and microstructure characteristics of the product, divided into three chapters.